Sedimentological and petrographic analysis of Neogene quaternary continental deposits in Argoub Kemellal Oum El Bouaghi northeastern Algeria evidence for a fluvial to lacustrine transition - Meguellati, Asma; Djerrab, Abderrezak; Khiari, Abdelkader; Gallet, Xavier; Dinar, Haythem; Garah, Abdelmoumen; Riheb, Hadji; Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Nadeem A., Khan (Springer Nature, 2026)
The Argoub Kemellal dome, located south of Oum El Bouaghi in northeastern Algeria, preserves a rich sedimentary archive documenting the paleoenvironmental evolution of the Neogene-Quaternary period. This study aims to reconstruct the paleogeographic development of the region by examining the interplay between sedimentary processes and environmental changes, particularly the transition from fluvial to lacustrine conditions. A multidisciplinary approach combining petrographic and sedimentological analyses was applied. Techniques included granulometric and calcimetric measurements, thin-section petrography, and both morphoscopic and scanning electron microscope (SEM) studies of quartz grains. The geological sequence comprises Miocene-aged detrital deposits overlain by Pliocene to Quaternary carbonate formations. Sedimentary formations document a transition from high-energy fluvial conditions to calmer lacustrine environments, driven by climatic change. Notably, calcium carbonate (CaCO3) content increases upward from 13% at the base to 57% at the top, highlighting the shift toward carbonatedominated lacustrine sedimentation. These results illustrate how climate forcing shaped sedimentary environments over time and contribute to reconstructing the Neogene-Quaternary paleogeography of the studied region. The finding underscores the value of continental deposits as sensitive geological archives of past environmental and climatic conditions.